2021
DOI: 10.1002/celc.202100957
|View full text |Cite
|
Sign up to set email alerts
|

Two‐Step Deposition Approach for Lead Free (NH4)3Sb2I9 Perovskite Solar Cells with Enhanced Open Circuit Voltage and Performance

Abstract: In recent years, development of lead (Pb) free perovskite solar cells (PSCs) has attracted the scientific community because of their stability in air and less toxic nature. Antimony (Sb) based perovskite like‐materials such as (CH3NH3)3Sb2I9 and (NH4)3Sb2I9 have been employed as light absorbers and showed promising features for photovoltaic applications. Herein, we have utilized (NH4)3Sb2I9 as light absorber for the construction of Pb free PSCs. Moreover, we have employed a modified two step procedure for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 49 publications
1
29
0
Order By: Relevance
“…We have compared our findings with recent literature in Table 1. The obtained results showed that our findings are comparable with previous reports [33–45] …”
Section: Resultssupporting
confidence: 93%
“…We have compared our findings with recent literature in Table 1. The obtained results showed that our findings are comparable with previous reports [33–45] …”
Section: Resultssupporting
confidence: 93%
“…Lead halide-based perovskite materials have been used in the fabrication of tandem solar cells, but the presence of toxic lead (Pb) still remains a concern for their practical applications [ 19 ]. In further studies, Pb-free perovskite materials such as methyl ammonium bismuth iodide, methyl ammonium antimony iodide, methyl ammonium tin iodide (MASnI 3 ), or methyl ammonium germanium iodide (MAGeI 3 ) have been explored in the construction of single-junction PSCs or tandem solar cells [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ]. The reports suggested that Sn- or Ge-based perovskite materials have excellent optoelectronic features and a less toxic nature [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…[9] In this connection, various light absorber materials such as CH 3 NH 3 SnX 3 , CH 3 NH 3 GeX 3 , (CH 3 NH 3 ) 2 Bi 2 I 9 , (NH 4 ) 2 Bi 2 I 9 , (NH 4 ) 2 Sb 2 I 9 , (CH 3 NH 3 ) 2 Sb 2 I 9 , Cs 3 Bi 2 I 9 , Cs 3 Sb 2 I 9 , C 6 H 4 NH 2 CuBr 2 I, CsSnX 3 , CsGeX 3 , and C 6 H 4 NH 2 CuCl 2 I have been explored in the construction of PSCs. [10][11][12][13][14][15][16][17][18][19][20][21][22] The previous reports showed that tin or germanium based perovskite materials are highly moisture sensitive and less stable than that of the Pb based perovskite materials. [23,24] Other perovskite-like materials such as Cs 3 Sb 2 I 9 or Cs 3 Bi 2 I 9 are air stable but their PCE is still far away than that of the Pb based PSCs.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of volatile and hygroscopic nature in the absorber layer is responsible for poor aerobic stability of CH 3 NH 3 PbX 3 and NH 2 CH 3 NH 2 PbX 3 perovskite materials [9] . In this connection, various light absorber materials such as CH 3 NH 3 SnX 3 , CH 3 NH 3 GeX 3 , (CH 3 NH 3 ) 2 Bi 2 I 9 , (NH 4 ) 2 Bi 2 I 9 , (NH 4 ) 2 Sb 2 I 9 , (CH 3 NH 3 ) 2 Sb 2 I 9 , Cs 3 Bi 2 I 9 , Cs 3 Sb 2 I 9 , C 6 H 4 NH 2 CuBr 2 I, CsSnX 3 , CsGeX 3 , and C 6 H 4 NH 2 CuCl 2 I have been explored in the construction of PSCs [10–22] . The previous reports showed that tin or germanium based perovskite materials are highly moisture sensitive and less stable than that of the Pb based perovskite materials [23,24] .…”
Section: Introductionmentioning
confidence: 99%